UMP introduces 4 student assistance incentives - Siti Nur Azwin, Zulkapri (2020)
Pekan, 27 October 2020 – The need for devices and internet access is crucial in undergoing online teaching and learning (T&L) activities, even more so in the COVID-19 pandemic, which has no signs of fully letting up soon.